Enzymatic extract from flowers of Algerian spontaneous Cynara cardunculus: Milk‐clotting properties and use in the manufacture of a Camembert‐type cheese. (2nd October 2018) - Zikiou, Abdellah; Zidoune, Mohammed Nasreddine
Abstract : The aim of this study was to assess the coagulant properties of crude extract from cardoon flowers (CECF) as a replacement for the imported coagulants used in the local Algerian cheese factories. Optimal coagulation activity of the extract was observed at pH 5 and 60 °C with a CaCl2 concentration of 0.02 M. The electrophoretic pattern revealed that the crude extract contains mainly cardosins A and B. The study of interactions involved in the formation of milk gel coagulated by CECF showed that hydrogen forces, hydrophobic interactions and calcium bridges contributed highly to the formation of milk gel. Camembert‐type cheese obtained by CECF was judged by trained panellists and was found to be in agreement with standard specifications. The present study highlights the possibility of using Algerian CECF as a promising plant coagulant in cheesemaking for the dairy industry.